Estimasi Stok Karbon Pada Tegakan Karet Di Atas Permukaan Tanah Kebun Sekolah: Studi Kasus Di SMKN 4 Sampit Kalimantan Tengah: Above-Ground Carbon Stock Estimation in Rubber Vegetation of School Gardens: A Case Study at SMKN 4 Sampit, Central Kalimantan - Anung Rachmad Basuki; Petrus Poerwadi; Renhart Jemi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Rubber plantations (Hevea brasiliensis Müll. Arg.) play an important role in carbon sequestration in tropical regions, including educational land. This study aims to estimate the above-ground biomass (AGB) carbon stock in rubber vegetation at the school garden of SMKN 4 Sampit, Central Kalimantan, using the allometric equation of Chave et al. (2005) with specific wood density correction for Hevea brasiliensis. Data were collected from three 20 m × 20 m measurement plots (400 m² each) with a total of 58 rubber trees. Measured parameters included diameter at breast height (DBH) and tree height. Results showed a mean AGB of 25.37 ± 4.66 Ton ha⁻¹ and a mean carbon stock of 11.92 ± 2.19 Ton C ha⁻¹, equivalent to 43.73 Ton CO₂e ha⁻¹. Carbon stock varied among plots, with Plot 2 being the highest (14.43 Ton C ha⁻¹) and Plot 3 the lowest (10.40 Ton C ha⁻¹). Differences among plots were attributed to variations in DBH, tree height, and stand density. Carbon stock values are consistent with intermediate-age rubber stands and indicate significant carbon storage potential in educational land. This study contributes to the carbon database of Indonesian tropical forests and supports the implementation of REDD+ programs at the site level.